2020
DOI: 10.1073/pnas.2000053117
|View full text |Cite|
|
Sign up to set email alerts
|

Accumulation of high-value bioproducts in planta can improve the economics of advanced biofuels

Abstract: Coproduction of high-value bioproducts at biorefineries is a key factor in making biofuels more cost-competitive. One strategy for generating coproducts is to directly engineer bioenergy crops to accumulate bioproducts in planta that can be fractionated and recovered at biorefineries. Here, we develop quantitative insights into the relationship between bioproduct market value and target accumulation rates by investigating a set of industrially relevant compounds already extracted from plant sources with a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 57 publications
3
65
0
Order By: Relevance
“…In a circular economy, monomers should be recovered and re-usable for subsequent polymerization without adversely affecting material quality. However, the combination of low market value and poor accumulation rates of plantbased plastics might represent an insurmountable challenge in the short run, favoring the production of higher-value coproducts from biomass (117). In that regard, chemical modifications of lignins into high-value products, such as aromas, flavors and essential oils, represents a potential economic incentive for biorefineries (78,118).…”
Section: Utilizing Sugars and Aromatics For Highervalue Co-productsmentioning
confidence: 99%
“…In a circular economy, monomers should be recovered and re-usable for subsequent polymerization without adversely affecting material quality. However, the combination of low market value and poor accumulation rates of plantbased plastics might represent an insurmountable challenge in the short run, favoring the production of higher-value coproducts from biomass (117). In that regard, chemical modifications of lignins into high-value products, such as aromas, flavors and essential oils, represents a potential economic incentive for biorefineries (78,118).…”
Section: Utilizing Sugars and Aromatics For Highervalue Co-productsmentioning
confidence: 99%
“…Recently, the overproduction of limonene has been successfully demonstrated in oilseed crop (Camelina sativa) by overexpressing LMS under the control of Arabidopsis promoters [286]. A recent study indicated that reaching limonene titers of 2.2% DW in bioenergy crops and extracting this coproduct from biomass at 70% efficiency could positively impact the economics of advanced biofuels [8].…”
Section: R-limonene (C 10 H 16 Monoterpene)mentioning
confidence: 99%
“…In addition, CRISPR/Cas9 genome editing has been demonstrated in rubber dandelion, which provides an avenue to accelerate the investigation of rubber biosynthesis [315]. Based on a techno-economic analysis, the accumulation of latex in bioenergy crops at titers of 2.2% DW could significantly improve the economics of second-generation biofuels [8].…”
Section: An Isoprenoid-derived Polymer Precursor: Natural Rubber ((C5mentioning
confidence: 99%
See 2 more Smart Citations